Effect of air flow rate and residence time on biodrying of cassava peel waste. (1st January 2015) - Sen, Ranjit; Annachhatre, Ajit P.
Effect of air flow rate and residence time on biodrying of cassava peel mixed with activated sludge waste was investigated at laboratory scale. Air flow rates of 0.01 to 0.04 m3 kg-1 h-1 and residence times of 12 to 20 days were maintained during biodrying process. Calorific value of cassava peel increased from its initial value of 4, 660 kJ kg-1 to a maximum value of 10, 406 kJ kg-1 (wet weight basis) when air flow rate of 0.03 m3 kg-1 h-1 and residence time of 16 days were maintained during biodrying. Under this operating condition, moisture content of cassava peel reduced from its initial value of 70.40% to a final value of 24.00%. Maximum feedstock temperature of 64.25°C at the top layer and 59.00°C at the bottom layer were recorded at this condition. Air flow rate of 0.03 m3 kg-1 h-1 with 16–day residence time was found optimum for biodrying of mixed materials yielding an increase of 123% in calorific value.